Concentration of lead and zinc in some brands milk and nutrients for babies - Amna K. Saber , Isma M. Abdolrhman , Masouda A. Arhuma (Journal of Pure & Applied Sciences, 2018)
This study aimed to estimate the lead and zinc component in 27 different samples of milk powder baby and some nutrients available in the local markets in the shite area. The results showed that the highest concentration of the studied elements in the milk samples was for the lead element compared to the zinc element. There was a significant difference in concentrations of the studied elements between the milk types and their age stages. However, this difference was not significant. The highest concentration of zinc and lead in Bebelac milk observed from six months to one year. For nutrients, lead concentrations increased more than zinc, especially in grain-containing nutrients, and the concentration of lead (3.8 mg / L) in the samples of Primalac milk against rehydration and the consumer in the age range from birth until the year. No significant differences observed between the concentration of zinc in both Primalac and Bebelac milk. The concentration of lead and zinc in children's milk powder was higher than the European standard and higher than the Egyptian standard.